Proteômica e potencial da atividade trombolítica da propriedade desfibrinogenante, in vivo, do veneno da Serpente Amazônica Crotalus durissus ruruima (Houge 1965). - Araújo, Thiago Ferreira de (2008)
An electrophoretic analysis, 1 – DE and 2 – DE, were detected of the venom of Crotalus durissus ruruima proteins with molecular masses of ~ 14, 32 and 50 kDA. By electrophoresis, SDS-PAGE tricine was detected a protein band of molecular mass of ~ 5 kDA that it suggests to understand to the crotamine. The activities phospholipase A2 and coagulant activity had been also detected in the venom of Crotalus durissus ruruima. Fractions of the venom of Crotalus durissus ruruima with coagulant activity, in vitro, under human fibrinogen and human plasma had been gotten by chromatography molecular exclusion and reverse phase. The coagulant activity gotten by the fractions was inhibited alone by PMSF, suggesting that the responsible toxin for the coagulant activity is one serinoproteinase. The proteolitic activity gotten by zimogram, using as bovine fibrinogen substratum, suggests the presence enzyme thrombin – like with molecular masses of the ~ 25 – 40 kDA. Of the coagulants, fractions gotten by chromatography reverse phase fraction (fraction 09) only presented defibrinating activity, in vivo, evaluated in mouse. This activity was not inhibited, in vivo, when this fraction previously was mix with human serum. Key words: Crotalus durissus ruruima, thrombin – like, defibrinating activity, coagulant activity, serinoproteinase